2019
DOI: 10.1097/olq.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

Male Partner Linkage to Clinic-Based Services for Sexually Transmitted Infections and Human Immunodeficiency Virus Services Following Couple Home-Based Education and Testing

Abstract: Background Home-based human immunodeficiency virus (HIV) testing and education has increased HIV test uptake and access to health services among men. We studied how a home-based antenatal intervention influenced male partner utilization of clinic-based HIV and sexually transmitted infection (STI) services, linkage to HIV care and medical circumcision. Methods We conducted a secondary analysis within a randomized controlled trial of pregnant women attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
4
0
3
Order By: Relevance
“…A US‐based quasi‐experimental study showed increased PrEP referral in the post‐intervention period among MSM receiving streamlined service delivery after post‐screening risk assessment [34]. In a Kenya‐based cohort study that involved contacting male partners of female ANC attendees, there was no improvement in VMMC linkage, though STI consultations were higher compared to the standard of care [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A US‐based quasi‐experimental study showed increased PrEP referral in the post‐intervention period among MSM receiving streamlined service delivery after post‐screening risk assessment [34]. In a Kenya‐based cohort study that involved contacting male partners of female ANC attendees, there was no improvement in VMMC linkage, though STI consultations were higher compared to the standard of care [35].…”
Section: Resultsmentioning
confidence: 99%
“…Gaps in WHO recommendations on linkage to prevention are summarized in Table 7. Studies conducted in Africa were all among heterosexual individuals and focused on linkage to PrEP, VMMC, STI and cervical cancer screening [26,28,29,31,33,35]. USbased studies evaluated PrEP linkage among key populations [27,30,32,34].…”
Section: Linkage To Preventionmentioning
confidence: 99%
“…Given the low incidence of HIV in CNC after CVCT, cost-benefit analyses preclude PrEP in this group. Similarly, given limited access and low uptake in many areas [ [72] , [73] , [74] ] men in concordant HIV- unions would be a lower programmatic priority for male circumcision compared with single men or men with HIV + spouses.…”
Section: Discussionmentioning
confidence: 99%
“…No processo de construção da revisão integrativa, seis fases foram utilizadas: 1. ferramenta para a educação em saúde 17,19 ; uma utilizava mensagens de texto 18 ; e outra usava materiais educativos 20 .…”
Section: Métodosunclassified
“…Além disso, as intervenções expostas pelos estudos nem sempre eram retratadas de maneira isolada, em que, apenas um estudo tratava puramente da intervenção 18 ; dois traziam a intervenção educativa como uma das fases de um programa de intervenção 17,19 ; e um avaliava os materiais educativos 20 . Organizou-se um quadro para que as informações acerca estudos pudessem ser sintetizadas (Quadro 1).…”
Section: Métodosunclassified